TRAINING FOR A CHOICE OF CAREER - DOSTÁL, Jiří (Trends in education, 2008)
The choice of career is a fundamental decision in life of every human being and it is necessary to pay a systematic attention to it. The contribution deals with substantial aspects connected with the choice of career, which must always proceed primarily from abilities and interests of an individual.
Keywords: Choice of career; career consulting; professional orientation.